"Sensory structures on the antennal flagella of two katydid species of the genus Mecopoda (Orthoptera, Tettigonidae)". (November 2016) - Schneider, Erik S.; Römer, Heinrich
Highlights: Identification of the same types of sensilla in both sexes and species. We found one uniporous, two aporous, and six multiporous sensilla. Seven sensilla were considered as chemosensory and two as potentially thermosensory. No sex-specific differences in typology, numbers or distribution of sensilla. Interspecific differences exist only in terms of the numbers of sensilla chaetica. Abstract: The typology, number and distribution pattern of antennal sensilla in two species of the genus Mecopoda were studied using scanning electron microscopy. The antennae of both sexes of both species attain a length of 10 cm. The antenna is made up of three basic segments: the scape, pedicel and flagellum, which is composed of more than 200 flagellomeres. We distinguished two types of sensilla chaetica, one type of sensilla trichodea, five types of sensilla basiconica and one type of sensilla coeloconica. The possible function of the sensilla was discussed. Six types of sensilla were considered as olfactory, one of which could also have a thermo- and hygrosensitive function. The remaining types of sensilla identified had a purely mechanosensory function, a dual gustatory- and mechanosensory function and a thermo- and/or hygrosensory function, respectively. Consistent sex specific differences in the types, numbers and distribution of antennal sensilla were not found. Interspecific differences were identified especially in terms of the numbers of sensilla chaetica.